The design of optimum composition for skimcoat cement using mixture experiment (case study of PT.X) - J Saragih (IPTEK Journal of Proceedings Series, 2018)
The purpose of this research was to obtain the optimum composition of cement mixture skimcoat., cement skimcoat is a building material used to polish concrete building walls made of 2-3 mm thick, as an indicator of the quality obtained from the company is shown by compressive strength, with a range of 7-10 N / mm2. to obtain the indicator, the mixture of scimcoat cement consists of three stages, first stage / mixed one with a mixed material : water, latex and pigment, the second stage / mixture of two with the ingredients : white cement, CaCO3 and fine aggregate, for the third stage / mixture of three is composed of a mixture of one, a mixture of two and a polymer. the method used in this research is mixture experiment. where the experimental point is obtained by the formula of randomization 2p-1 and three repetitions so that each trial consists of 21 experimental points.The optimum composition obtained for one skimcoat cement sack weigthing 30 kg is comprised of water of 21.91%, latex 2,6%, pigment 1,78%, white cement 15,12%, CaCO3 2,41%, fine aggregate 27,58% and polymer 2,5 %